PENINGKATAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL COOPERATIVE TIPE JIGSAW PADA PEMBELAJARAN TEMATIK TERPADU DI KELAS IV SDN 14 ATTS KOTA BUKITTINGGI - Miranti, Cici Ayu; Muhammadi, Muhammadi; Arwin, Arwin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2015)
This research background from student results is low on preparation of learning planning, it was found the problem of students lacking in critical thinking and students seemed less active in the learning process. From the observation from the teacher it appears that the learning process is still teacher-centered. The purpose of this study was to describe the improvement of integrated thematic learning outcomes using the jigsaw cooperative model in the class 4 grade of the 14 atts public elementary school in the city of bukittinggiThis research is class action (PTK) that use a qualitative and quantitative approach. Consisting of two meetings.performed in two cycles, is the i cycle consisting of 2 meetings, and the ii cycle consists of 1 meeting.in each cycle includes 4 stages, namely planning, implementation, observation, and reflection. The subject of this study were teachers and the 4th grade of the 14 atts public elementary school in the city of bukittinggi. The procedure of the research carried out is described as follows: planning, implementation, and learning outcomes using test observation techniques.The results showed an increase in: a.) The i cycle rpp 83.33% (good) and the ii cycle 91.67% (very good), b.) Implementation on the aspect of the teacher in the i cycle 81.24% (good) and cycle ii 94.44% (very vaik), while the implementation of aspects of the i cycle students 79.68% (good), and the ii cycle 91.67% (very good), c.) Assessment of attitudes in the first cycle to get a good attitude and cycle ii obtain very good attitude d) assessment of aspects of knowledge in the first cycle obtained 68.28 (sufficient) and cycle ii 81.46 (good). E) the assessment of the skills aspects in the first cycle obtained 71.58 (good) and this second cycle was 81.43 (good)..based on these results it can be concluded the jigsaw cooperative model can improve integrated thematic learning outcomes for students